Fingers Phrase Music Differently: Trial-to-Trial Variability in Piano Scale Playing and Auditory Perception Reveal Motor Chunking - Van Vugt, Floris T.; Jabusch, Hans-Christian; Altenmüller, Eckart (Frontiers in Psychology, 2012)
We investigated how musical phrasing and motor sequencing interact to yield timing patterns in the conservatory students' playing piano scales. We propose a novel analysis method that compared the measured note onsets to an objectively regular scale fitted to the data. Subsequently, we segment the timing variability into (i) systematic deviations from objective evenness that are perhaps residuals of expressive timing or of perceptual biases and (ii) non-systematic deviations that can be interpreted as motor execution errors, perhaps due to noise in the nervous system. The former, systematic deviations, reveal that the two octave scales are played as a single musical phrase. The latter, trial-to-trial variabilities reveal that pianists' timing was less consistent at the boundaries between the octaves, providing evidence that the octave is represented as a single motor sequence. These effects cannot be explained by low-level properties of the motor task such as the thumb-passage and also did not show up in simulated scales with temporal jitter. Intriguingly, this instability in motor production around the octave boundary is mirrored by an impairment in the detection of timing deviations at those positions, suggesting that chunks overlap between perception and action. We conclude that the octave boundary instability in the scale playing motor program provides behavioural evidence that our brain chunks musical sequences into octave units that do not coincide with musical phrases. Our results indicate that trial-to-trial variability is a novel and meaningful indicator of this chunking. The procedure can readily be extended to a variety of tasks to help understand how movements are divided into units and what processing occurs at their boundaries.